Generalization of response interruption and redirection procedure with vocal stereotypy. (5th July 2021) - Barszcz, Holly; Griffith, Annette K.; Weigand, Patricia; Garcia, Yors
Abstract: This study used a combined design to evaluate the effects of nonvocal demands on vocal stereotypy in novel locations by implementing a concurrent multiple baseline design across settings, replicated across all participants. Results indicated that both the traditional and modified response interruption and redirection (RIRD) intervention were effective at reducing occurrences of vocal stereotypic behaviors for all four participants. The traditional RIRD intervention initially resulted in a larger decrease of these behaviors than the modified RIRD intervention; however, by the end of the study, the effects of both interventions on occurrences of vocal stereotypic behaviors were similar. Additionally, the effects of the RIRD intervention on occurrences of vocal stereotypic behavior met mastery criteria and generalized across settings for all four participants. The RIRD intervention generalized to the additional setting in less time than it took for the RIRD intervention to be effective in the first setting for all four participants.